Designing Mars Missions for the Utilization of Rotorcraft - Gelhar, Sophie R (Proceedings of the Wisconsin Space Conference, 2020)
Following the technical demonstration of the Mars Helicopter on the Mars 2020 mission, interest in further exploration of Mars utilizing rotorcraft is expected to increase. Previously, scientific exploration has been limited by the resolution of instruments on satellites and the terrain a rover can traverse. Rotorcraft enable exploration in previously inaccessible locations with increased efficiency compared to rovers and improved resolution (compared to satellites). This paper describes missions designed to utilize the unique capabilities of rotorcraft in order to advance the science performed extraterrestrially. For Mars this includes tasks such as determining if Mars ever supported life, understanding climate processes and history, determining the evolution of Martian geology, and preparing for human exploration. The missions fall into three general categories: rover assistance, sample collection, and data collection. Complimentary concept vehicles are also discussed. This paper is meant to serve as a reference, resource, and starting point for the future exploration of Mars with rotorcraft.